2013
DOI: 10.1007/s11284-013-1053-x
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the timing of vessel formation and leaf phenology in ten ring‐porous and diffuse‐porous deciduous tree species

Abstract: The goal of this study is to clarify how different aspects of plant function are coordinated developmentally for species of ring‐porous versus diffuse‐porous deciduous trees, comparing the timing of leaf phenology and vessel formation in twigs and stems from an ecophysiological viewpoint. Cylindrical stem cores and twigs were collected at intervals from early spring through summer from five ring‐porous and five diffuse‐porous species in a cool temperate forest, and leaf and vessel formation were observed simul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(57 citation statements)
references
References 26 publications
5
50
1
1
Order By: Relevance
“…Differences in the delays between the spring phenophases of wood and leaves are also observed from year to year (Takahashi et al 2013) and among individuals within species (N. Delpierre, unpublished results). From this ensemble of results, it is difficult to infer the influence of auxin produced in swelling or elongating buds on the timing of the onset of cambium division.…”
Section: Integrated Phenology At the Tree Scalementioning
confidence: 82%
“…Differences in the delays between the spring phenophases of wood and leaves are also observed from year to year (Takahashi et al 2013) and among individuals within species (N. Delpierre, unpublished results). From this ensemble of results, it is difficult to infer the influence of auxin produced in swelling or elongating buds on the timing of the onset of cambium division.…”
Section: Integrated Phenology At the Tree Scalementioning
confidence: 82%
“…In ash by around April 20th, some large earlywood vessels had already formed (Frankenstein et al 2005). Generally, in ring-porous trees, the first earlywood vessels are formed 2-6 weeks before bud break (Suzuki et al 1996;Kudo et al 2015), and it is also worth emphasizing that the lignification of the first-formed vessels in stems was observed from 2 weeks before, up to 4 weeks after, leaf appearance (Takahashi et al 2013). Thus, the timing of leaf and growth phenologies is species specific, leading to differences in carbon allocation (e.g.…”
Section: Relationships Between Leaf Phenology and Earlywood-vessel Fomentioning
confidence: 94%
“…Thus, the timing of leaf and growth phenologies is species specific, leading to differences in carbon allocation (e.g. Suzuki et al 1996;Takahashi et al 2013).…”
Section: Relationships Between Leaf Phenology and Earlywood-vessel Fomentioning
confidence: 99%
“…Previous studies revealed that the timing of vessel formation in relation to leaf appearance in typical ring-porous deciduous species differs from that in typical diffuse-porous species (Ladefoged 1952;Suzuki et al 1996Suzuki et al , 2000Takahashi et al 2013Takahashi et al , 2015. The first-formed vessels, which develop new rings adjacent to the annual ring border, mature around the time of leaf appearance in stems of ring-porous species (Zasada & Zahner 1969;Suzuki et al 1996Suzuki et al , 2000Sass-Klaassen et al 2011;González-González et al 2013;Takahashi et al 2013;Kudo et al 2015).…”
Section: Introductionmentioning
confidence: 98%